Measurement and purification of Alanine aminotransferase (ALT) enzyme activity in patients with celiac disease (Baghdad Science Journal, 2017)
Celiac disease (CD) is the most common genetically - based disease in correlation with food intolerance. The aim of this study is to measure the activity of ALT enzyme and purify enzyme from sera women with celiac disease. Alanine aminotransferase (ALT) activity has been assayed in (30) women serum samples with celiac disease, age range between (20-40) year and (30) serum of healthy women as control group, age range between (22-38) year. In the present study, the mean value of ALT activity was significantly higher in patients with celiac disease than healthy group (p